2014
DOI: 10.1177/0165025413515627
|View full text |Cite
|
Sign up to set email alerts
|

Will they like me? Adolescents’ emotional responses to peer evaluation

Abstract: Relative to children and adults, adolescents are highly focused on being evaluated by peers. This increased attention to peer evaluation has implications for emotion regulation in adolescence, but little is known about the characteristics of the evaluatee and evaluator that influence emotional reactions to evaluative outcomes. The present study used a computer-based social evaluation task to examine predictors of adolescents’ emotional responses to feedback from unknown peers. Nine-to-seventeen-year-olds (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 44 publications
(69 reference statements)
2
54
0
2
Order By: Relevance
“…Such affective variables may negatively shape middle school students' attitudes toward mathematics (Ma & Kishor, 1997), as well as their experiences within the classroom. In addition, students at this age possess a desire to be accepted by their peers (Guyer, Caouette, Lee, & Ruiz, 2014), hold a heightened awareness of how one looks (Wigfield & Wagner, 2005), and a need to build appropriate and supportive relationships with their teacher (McHugh, Horner, Colditz, & Wallace, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such affective variables may negatively shape middle school students' attitudes toward mathematics (Ma & Kishor, 1997), as well as their experiences within the classroom. In addition, students at this age possess a desire to be accepted by their peers (Guyer, Caouette, Lee, & Ruiz, 2014), hold a heightened awareness of how one looks (Wigfield & Wagner, 2005), and a need to build appropriate and supportive relationships with their teacher (McHugh, Horner, Colditz, & Wallace, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent neuroimaging studies in adolescents between 11 and 19 years of age have confirmed that, when observed by peers, young adolescents show a weaker activation of brain areas associated with cognitive control and instead show higher neuronal activity in regions associated with rewards, which explains the youngsters' need to actively seek acceptance of their social group (Brodbeck et al, 2013;Chein et al, 2011;Guyer et al, 2014;Steinberg, 2008). The phenomenon of regulatory difficulty before social stimuli has also proved to be associated with a higher occurrence in risk behaviors such as substance use, and risky sex behaviors, among others (Brodbeck et al, 2013;Chein et al, 2011;Guyer et al, 2014;Steinberg, 2008). …”
Section: -8 Yearsmentioning
confidence: 98%
“…Researchers in this field have managed to locate the full maturation of these neurobiological systems towards the end of adolescence. Researchers also explain that it is near the end of adolescence that, even under highly emotional arousal, individuals successfully demonstrate sophisticated self-regulation skills that enable them to control impulses and cope with stressors in a socially adequate manner (Chein, Albert, O'Brien, Uckert, & Steinberg, 2011;Guyer, Caouette, Lee, & Ruiz, 2014;Lewis et al, 2006;Luna et al, 2010;Ochsner & Gross, 2005;Steinberg, 2008;Thompson, 2011;Zimmermann & Iwanski, 2014 (Campos et al, 2004;Cole, 2014;Goldsmith & Davidson, 2004;Thompson, 2011;Thompson et al, 2013;Zeman et al, 2006).…”
Section: Influences In the Development Of Emotional Regulationmentioning
confidence: 99%
See 2 more Smart Citations